Digital empowerment and trade-embodied carbon intensity: insights from value-added decomposition in services - Qiao Jin; Wanying Tian; Zhida Jin (Humanities & Social Sciences Communications)
Abstract Trade-related carbon emissions have emerged as a significant environmental challenge, yet strategies to mitigate their impact remain underexplored. This paper examines the role of digital empowerment in reducing the trade-embodied carbon intensity of services, with a focus on a value-added trade approach. Using panel data from 67 economies spanning from 1995 to 2018, this paper empirically demonstrates that digital empowerment significantly lowers trade-embodied carbon intensity in services. Key mechanisms driving this reduction include scale effects, intra-industry enhancements, and trade structure optimizations. Our findings reveal that both domestic and foreign digital empowerment sources positively impact trade-embodied carbon intensity reduction, with a more pronounced effect in developing economies compared to developed ones. This study advances the understanding of how the digital economy influences the carbon competitiveness of services and provides critical insights for policymakers in crafting service trade and green development strategies.